PERSPEKTIF MAQASHID AS SYARI’AH TERHADAP NAFKAH ORANG TUA KEPADA ANAK YANG SUDAH MENIKAH STATUS PELAJAR - SAMSUL ARIFIN (Minhaj: Jurnal Ilmu Syariah, 2023)
Abstract: Parents have more affection for their children, so it is appropriate for parents to be called unsung heroes and become the first madrasa in a child's education. Whatever the wishes of the child must be followed by the parents including the tuition fees. Even so, it is actually the responsibility of parents, but there is a limit, namely that parents are obliged to provide for their children until the extent that they are married. However, some children get married during the student period so all the needs in the family ask their parents, be it school fees or the cost of their daily lives. The purpose of this study is to respond to these problems in terms of Maqashid As-Shari'ah by using the kuliatative method and making observations to several respondents so as to produce accurate data and provide solutive to the community. Al As a result, parents can provide for their children who are married as students with a record of not feeling burdened and their own lives fulfilled. Although parents provide their children's livelihood, they should not interfere with the child's family problems. And parents how to give freedom to their children to live independently with their families by providing a house to build a new familyAbstrak: Orang tua mempunyai kasih sayang yang lebih kepada anaknya, sehingga pantaslah orang tua disebut pahlawan tanpa tanda jasa serta menjadi   madrasah pertama dalam pendidikan seorang anak. Segala apapun keinginan anak pasti diikuti oleh orang tua termasuk biaya sekolahnya. Walaupun hal demikian, sebenarnya menjadi tanggung jawab orang tua namun ada batasannya yaitu orang tua wajib memberikan nafkah anaknya sampai batas mereka menikah. Akan tetapi sebagian anak menikah pada masa-masa pelajar jadi segala kebutuhan apapun dalam keluarga mintak kepada orang tuanya baik itu baiaya sekolah maupun biaya kehidupan sehari-harinya. Tujuan penelitian ini untuk merespon permasalahan tersebut ditinjau dari Maqashid As-Syari’ah dengan menggunakan metode kuliatatif serta melakukan observasi kepada beberapa responden sehingga menghasilkan data yang akurat serta memberi solutif kepada masyarakat. Al Hasil, orang tua boleh memberikan nafkah anaknya yang menikah status pelajar dengan catatan tidak merasa terbebani dan kehidupannya sendiri tercukupi. Walaupun orang tua memberikan nafkah anaknya akan tetapi tidak boleh ikut campur terhadap permasalahan keluarga anak. Dan orang tua bagaimana harus memberi kebebasan kepada anaknya agar hidup mandiri bersama keluarganya dengan cara disediakan rumah untuk membangun keluarga baru Keywords : Maqashid As-Shari'ah, Livelihood, Parents and Children